Age differences in the behavioural economics of cannabis use: Do adolescents and adults differ on demand for cannabis and discounting of future reward?. (1st September 2022) - Borissova, A.; Soni, S.; Aston, E.R.; Lees, R.; Petrilli, K.; Wall, M.B.; Bloomfield, M.A.P.; Mertzani, E.; Paksina, A.; Freeman, T.P.; Mokrysz, C.; Lawn, W.; et al.
Abstract: Background: Adolescence is a period of psychological and neural development in which harms associated with cannabis use may be heightened. We hypothesised that adolescent who use cannabis (adolescentsWUC) would have steeper delay discounting (preference for immediate over future rewards) and greater demand (relative valuation) for cannabis than adults who use cannabis (adultsWUC). Methods: This cross-sectional study, part of the 'CannTeen' project, compared adultsWUC (n = 71, 26–29 years old) and adolescentsWUC (n = 76, 16–17 years old), and gender- and age-matched adolescent (n = 63) and adult (n = 64) controls. AdolescentsWUC and adultsWUC used cannabis 1–7 days/week and were matched on cannabis use frequency (4 days/week). The Monetary Choice Questionnaire assessed delay discounting. A modified Marijuana Purchase Task (MPT) assessed cannabis demand in adolescentsWUC and adultsWUC. The MPT yielded five indices: intensity (amount of cannabis used at zero cost), O max (total peak expenditure), P max (price at peak expenditure), breakpoint (cost at which cannabis demand is suppressed to zero) and elasticity (degree to which cannabis use decreases with increasing price). Analyses were adjusted for covariates of gender, socioeconomic status, other illicit drug use. Results: Both adolescentsWUC and adultsWUC had steeper delay discounting than controls ( F, (1, 254)= 9.13, p = 0.003, η p 2 = 0.04), with no significant age effect or interaction. AdolescentsWUC showed higher intensity ( F, (1, 138)= 9.76, p = 0.002, η p 2 = 0.07) and lower elasticity ( F, (1, 138)= 15.25, p < 0.001, η p 2 = 0.10) than adultsWUC. There were no significant differences in P max, O max or breakpoint. Conclusion: Individuals who use cannabis prefer immediate rewards more than controls. AdolescentsWUC, compared to adultsWUC, may be in a high-risk category with diminished sensitivity to cannabis price increases and a greater consumption of cannabis when it is free. Highlights: Cannabis users (CU) showed steeper delay discounting than age-matched controls. Adolescent CU have higher intensity of cannabis demand than adults. Adolescent CU have lower elasticity of cannabis demand than adults. Both user groups show a behavioural economic profile that may underlie CUD.